Rationality of Society RASIONALITAS MASYARAKAT PETEMON DALAM MEMILIH BERBELANJA DI PASAR TRADISIONAL PASCA PEMBANGUNAN PASAR MODERN: RASIONALITAS MASYARAKAT PETEMON DALAM MEMILIH BERBELANJA DI PASAR TRADISIONAL PASCA PEMBANGUNAN PASAR MODERN (Studi Kalangan Sosial Ekonomi Atas di Wilayah Petemon) - Jannah, Miftakhul (Paradigma, 2021)
A traditional market is a place sellers and buyers to do the economy activity. The individual conducting consumption in the marketinto a social action. This is Because there are motivation of individuals shopping at traditional market to reach the purpose. This research is the kind of kualitatif research with the approach verstehen. The perspective theory of the research used the theory of social action by Max Weber. Subject were selected by purposive technique. This research using data primary and data secondary. Analysis data in this research used analysis interactive of Matthew B. Miles dan Michael Huberman. The results of the research shows that Petemon public splits into three, this is origin, reminds people and migrants. The social-economy of the origin and remaind people include the category of high social-economy. This jobs is teachers, employees, until the entrepreneur. Range of income start from Rp.4.000.000,00 to Rp.20.000.000,00. Have a lot income, but people choose shopping at a traditional market. The activity of shopping at the traditional market is still being done despite a lot of the modern market adjacent to the settlement. The activity of consumption have a many reasons, including: (1) Instrumentally rational action, doing because factors of price and location of the market, (2) Value rational action, doing because social value to help a people, (3) traditional action, doing because a tradition of the family, (4) affectual type doing if there was a sudden purposes. Fourth action is doing by the Petemon people when shopping at a traditional market.